The critical role of SENP1-mediated GATA2 deSUMOylation in promoting endothelial activation in graft arteriosclerosis - Cong Qiu (Nature Portfolio, 2017)
A major cause of transplanted organ failure is graft arteriosclerosis. Qiuet al. show that a key protease of post-translational SUMO modification, SENP1, is crucial for graft arteriosclerosis by regulating the activity of GATA2 transcription factor in the endothelium, and promoting endothelial inflammation and alloimmunity.